Automated diagnosis of misconceptions about electricity what are the prospects? - Brna, Paul; Howe, Jim (1991)
Abstract: "Detecting that a student has made an error is typically easier than accounting for the error. Determining any underlying beliefs that contribute to the occurrence of an error is a difficult business both for the student and for the teacher. In automating this process, we face some further difficulties. We are in the process of building a system, CARoM, that is to be capable of diagnosing student's misconceptions within the domain of building simple electrical circuits. Eventually, we hope to exploit this information in a larger system. The motivation for this paper stems from a need to assess what has been achieved and the limits of what can reasonably be achieved within an essentially constructive approach
Keywords: Education and training; Electronics and electrical engineering, computer science; Computer-assisted instruction